Patients and families experience with pharmacist care at cystic fibrosis foundation accredited clinics. Issue 8 (7th May 2019) - Young, David C.; Autry, Elizabeth; Zobell, Jeffery T.; Kormelink, Lauren; Homa, Karen; Sabadosa, Kathryn A.; Kanga, Jamshed; Anstead, Michael; Kuhn, Robert
Abstract: Cystic fibrosis (CF) is a complex genetic, multiorgan disease. The CF Foundation (CFF) recommends a multidisciplinary team (physician, nurse, respiratory therapist, dietitian, physical therapist, social worker, mental health coordinator, clinic coordinator, and pharmacist) to work with patients and families. The objective of our study was to describe the impact of a pharmacist involved in the care of patients and families from their perspective. The CF Patient and Family Experience of Care (PFEC) is a voluntary, 50‐question telephonic or internet‐based survey designed to continuously collect information from patients and their families regarding their care experience. From August of 2017 through February of 2018, five questions were added to the internet survey to assess the impact of the pharmacist on the care experience. From the 666 respondents, 54% reported that a pharmacist was involved in their CF care. At two CF clinics designated as "full access" to a pharmacist, respondents reported a higher percentage of the CF–team discussed medications compared to those from three clinics designated as "limited access" to the pharmacist (95% vs 67%). Respondents in clinics with "full access" to a pharmacist were significantly more likely to get their medications refilled on time (78% vs 63%) and reported using fewer pharmacies to fill their medications. Pharmacist involvement in CF care may improve patient's access to medication and the ability to sustain use.